Phytochemical and Pharmacognostical Investigations on Aerial roots of Ficus lacor Buch. Ham - Rakesh Kumar Sindhu; Sandeep Arora (International Journal of Phytomedicine, 2013)
Objective: To evaluate Phytochemical and pharmacognostical investigations on the aerial roots of Ficus lacor Buch. Ham. Methods: The investigations as per WHO Guidelines and other standard parameters (Morphological studies, Microscopical studies, Histochemical colour reaction Extractive values, Ash values, Swelling index , bitterness value, foaming index haemolytic activity, tannin content and phytochemical investigations) Results: The aerial roots are typical roots, fibrous and slightly bitter. The microscopy of the powder revealed the presence of annular xylem vessel, lignified fibre, parenchymatous cell and cork cells. Total ash, acid insoluble ash, water insoluble ash and sulphated ash were 14.15%, 8.57%, 10.75%, 6.00% respectively. The extractive values i.e. petroleum ether, chloroform, ethyl acetate, ethanol and aqueous extract were 5.7%, 10%, 5.5%, 4.5%, 10.5%. The fiber content was 9.45%. The plant can be used as bitter as its bitterness was found to be 1.9 unit/g. The foaming index was 124.6. The plant possesses haemolytic activity. The plant extracts were good to be free of microbial contamination. The tannin content was 22. The preliminary phytochemical screening of Petroleum Ether extract, Ethyl acetate extract, Chloroform extract, Ethanol extract, Aqueous extract was performed. The presence of flavonoids, carbohydrates, saponins, phenolic compounds, and sterol in various extracts were observed. The alcoholic and aqueous extracts were screened for presence of amino acid and carbohydrates. The TLC profile of extracts showed the presence of three amino acid viz. alanine, methionine, ornithine and tyrosine and three carbohydrates i.e. galactose, lactose and sucrose. Conclusion: This is first ever phytochemical and pharmacognostical study carried out on the aerial roots of Ficus lacor Buch. Ham. useful for future standardization of Ficus lacor aerial roots.